Pengaruh Penjadwalan Dan Fasilitas Pemuatan Terhadap Waktu Tunggu Kapal Pada Transshipment Muara Berau Di PT Indo Tambangraya Megah - Oceania, Siti Annisafa; Larasti, Wenny Ananda; Handayani, Melia (Universitas Pakuan, 2025)
THE EFFECT OF SCHEDULING AND LOADING FACILITIES ON SHIP WAITING TIME ON MUARA BERAU TRANSSHIPMENT AT PT INDO TAMBANGRAYA MEGAHThis study aims to analyze the influence of Vessel Scheduling and Loading Facilities on Vessel Waiting Time in the transshipment operations of PT Indo Tambangraya Megah Tbk at Muara Berau. The main operational issue identified is the high incidence of waiting cargo and waiting loading facilities, which prevents vessels from being served immediately upon arrival. This condition leads to increased waiting time and demurrage charges. The study employs a quantitative survey approach using primary and secondary data, and shipment documentation from January to March 2025. Data analysis was conducted through classical assumption tests and multiple linear regression to assess both simultaneous and partial effects of the independent variables. The findings indicate that Vessel Scheduling and Loading Facilities jointly have a significant influence on Vessel Waiting Time. However, partially, only the Loading Facilities variable shows a significant effect, whereas Scheduling does not significantly reduce waiting time. These results reflect real operational conditions where well-prepared schedules cannot be fully realized due to equipment downtime and limitations in loading capacity. The coefficient of determination, 60.3%, demonstrates that most variations in vessel waiting time are explained by the two variables. Overall, the study concludes that improving the readiness and capacity of loading facilities is the most dominant factor in reducing vessel waiting time in transshipment operations at Muara Berau.